Evaluation of a collagen-bioaggregate composite scaffold in the repair of sheep pulp tissue - Burak Dayı; Deniz Sezlev Bilecen; Hatice Eröksüz; Muhammet Yalçın; Vasıf Hasırcı (European Oral Research)
Purpose: This study aimed to compare the effects of the collagen-BioAggregate mixture (CBA M) and collagen-BioAggregate composite (CBA-C) sponge as a scaffolding material on the reparative dentin formation. Materials and methods: CBA-C sponge (10:1 w/w) was obtained and characterized by Scanning Electron Microscopy (SEM) and Mercury Porosimetry. Cytotoxicity of the CBA-C sponge was tested by using the L929 mouse fibroblast cell line. Dental pulp stem cells (DPSCs) were isolated from the pulp tissue of sheep teeth and characterized by flow cytometry for the presence of mesenchymal stem cell marker, CD44. The osteogenic differentiation capability of isolated DPSCs was studied by Alizarin Red staining. The cells were then used to study for the compatibility of CBA-C sponge with cell proliferation and calcium phosphate deposition. The effect of CBA-C sponge and CBA-M on the induction of dentin regeneration was studied in the perforated teeth of sheep for the eight-week period. All the analyses were performed with appropriate statistical hypothesis tests.Results: CBA-C sponge was found to be biocompatible for DPSCs. The DPSCs seeded on the CBA-C sponge were able to differentiate into the osteoblastic lineage and deposit calcium phosphate crystals in vitro. Reparative dentin formation was observed after the second week in the CBA-C sponge applied group. At the end of eight weeks, a complete reparative dentin structure was formed in the CBA-C sponge applied group, whereas necrotic tissue residues were observed in groups treated with the CBA-M. Conclusion: CBA-C sponge represents a better microenvironment for reparative dentin formation probably due to maintaining DPSCs and allowing their osteogenic differentiation and thus calcium phosphate deposition.